Peacock mites on cannon-ball tree, Couroupita guianensis (Lecythidaceae) in the Southeast Region of Brazil - Escobar-Garcia, Hector Alonso [UNESP]; de Andrade, Daniel Júnior [UNESP]; Beard, Jennifer J.; Ochoa, Ronald (Les Amis d'Acarologia, 2024)
Tuckerella ornata, Tuckerella knorri (Acari: Tuckerellidae) and Brevipalpus yothersi (Acari: Tenuipalpidade) were found associated with the native South American Cannonball tree, Couroupita guianensis, for the first time in Brazil. The trees were observed throughout their flowering season in spring for two consecutive years. The highest population densities of peacock and flat mites were located on the raceme-type inflorescences. Throughout this survey, no mites were detected on the fruits.
Keywords: Amazon Region; forest tree; landscape; Tetranychoidea; Trombidiformes